IMPLEMENTASI PROGRAM ASURANSI USAHA TERNAK SAPI/KERBAU (AUTS/K) DIKABUPATEN TANAH DATAR OLEH DINAS PERTANIAN - Indah Fadhilah; Rizki Syafril (LPPM Universitas Abdurrab, 2025)
This research aims to explain how the Cattle/Buffalo Livestock Business Insurance Program (AUTS/K) is implemented in Tanah Datar Regency. The method used in this research is a qualitative descriptive method with technical data analysis in the form of data reduction, data presentation, and drawing conclusions by selecting informants using purposive sampling techniques. The results of the research show that the implementation of the Cattle/Buffalo Livestock Business Insurance Program (AUTS/K) in Tanah Datar Regency has been implemented where the implementation of this program has provided benefits in the form of financial protection for farmers who experience losses due to death or loss of livestock. However, its implementation still requires further efforts to reach more breeders evenly. The AUTS/K program is a collaboration between the Ministry of Agriculture and the Tanah Datar Regency Government where 80% of the premium budget is given by the central government to Insurance Companies and 20% is covered by the Tanah Datar Regency APBD starting in 2022. Therefore, breeders who take part in the program no longer pay premiums to insurance companies, here the insurance company appointed is PT. Indonesian Insurance Services (Jasindo) which is also responsible for implementing the AUTS/K program. Furthermore, the implementation of this program also faces several significant challenges, especially in social and cultural aspects, such as the negative perception of breeders regarding the installation of ear tags which are considered to reduce the selling value of cattle. In addition, difficult geographical conditions and long distances between cages result in inefficiencies in supervision and monitoring